Yield and quality of beetroot to soil test crop response (STCR) - integrated plant nutrient system (IPNS) based fertilizer prescription in Ultisols of Western Ghats of Tamil Nadu, India - R Arulmani; K M Sellamuthu; S Maragatham; A Senthil; S P Thamaraiselvi; R Anandham; P Malathi; G Sridevi (Plant Science Today, 2024)
Beetroot is one of the most important root vegetable crops and is consumed globally due to its rich nutrient content. The current research was conducted on a farmer’s holding, using beetroot (Improved crystal hybrid) in Nilgiri district, Western Ghats of Tamil Nadu to study the effect of different N, P2O5, K2O and integrated plant nutrient system (IPNS) dosages in yield attributes and quality parameters. Two field trials were conducted in farmer's land at Kadanad Village (110 48’ N Latitude, 760 72’ E Longitudes) during the winter of 2024 and in Emerald Village (110 31’ N Latitude, 760 63’ E Longitudes) during the summer of 2024. The experiment was designed using a RBD with ten treatments and three replications. The treatments were absolute control, blanket, blanket + FYM, STCR-NPK based fertiliser dose for an yield target of 35, 40 and 45 t ha-1, soil test crop response - integrated plant nutrient system (STCR-IPNS) based fertiliser dose for an yield target of 35, 40 and 45 t ha-1 and farmer’s practice. The treatment of 180 N+233 P2O5+116 K2O Kg ha-1 along with FYM @12.5 t ha-1 (T3) recorded the highest plant height (51.59 cm), more number of leaves per plant (24.05), leaf width (18.14 cm), higher total chlorophyll (47.28), root yield (44.21 t ha-1) and quality parameters as total sugar (8.95%), reducing sugar (2.08%), non-reducing sugar (6.87%), total soluble solids (12.80 0B) and ascorbic acid (3.62 mg 100 g-1). The treatment receiving inorganic NPK fertilizers along with FYM @12.5 t ha-1 (T3) recorded the highest beetroot of yield of 44.21 t ha-1 than the soil test based inorganic fertilizer application treatment (T6). Fertilizer prescription based on STCR-IPNS model found to be better choice to enhance yield and quality of beetroot.